Multiple adverse drug reactions during all-trans retinoic acid treatment for acute promyelocytic leukemia: differentiation syndrome, bradycardia, intestinal necrosis - Valeria Ferla; Mariarita Sciumé; Umberto Gianelli2; Luca Baldini; Nicola Stefano Fracchiolla (Open Exploration Publishing Inc., 2020)
All-trans retinoic acid (ATRA) induces complete remission in a high proportion of acute promyelocytic leukemia (APL). Nevertheless it is be associated with adverse drug reactions that might be life-threatening including differentiation syndrome, myocarditis, myositis, Sweet's syndrome and ulcers. We describe a case of APL who during induction therapy developed ATRA syndrome, cardiac arrhythmia and multiple episodes of intestinal necrosis that required surgery. In particular, we report here for the first intestinal necrosis attributable to ATRA treatment in the absence of histological evidence of promyelocytes infiltration or leukocytoclastic vasculitis.